Using the WSA method for ARS application in the Czech Republic - Kučera, Petr; Šturma, Martin (Kaunas University of Technology, 2024)
The paper deals with the possibilities of the Automatic Route Setting System application in the Czech Republic. It proposes an original approach to evaluating the railway stations on the Czech railway network using the Weighted Sum Approach. In the paper, the authors define the criteria to be assessed within the Weighted Sum Approach and determine their weight. After the evaluation of the Weighted Sum Approach, the ranking of stations according to their suitability for the application of the Automatic Route Setting System will be determined in order to maximise the benefits of the Automatic Route Setting System. The aim of the paper is to propose a solution methodology and its application to a selected sample of several railway stations.
Využití metody WSA pro aplikaci ARS v České republice
Keywords: Automatic Route Setting System; Weighted Sum Approach; Automatické stavění vlakových cest; metoda váženého součtu (WSA)